STUDI ANALISIS KAPASITAS NOMINAL PELAT KOMPOSIT BETON-DEK BAJA METODE ULTIMIT, TEGANGAN KERJA DAN SDI-ANSI 2017 - Hariadi Yulianto (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2021)
Today, the most efficient slab construction method is the concrete-steel deck composite slab because there is no need to remove the deck after the concrete casting process. Nevertheless, reinforced concrete standard code (SNI 2847:2019) not emphasized a specific method to calculate the concrete-steel deck slab's nominal capacity. The code is embraced by the plastic method analysis, which is calculated the nominal capacity of the structure on the ultimate condition. However, several laboratory tests reveal a slip behavior between the concrete and steel deck before the slab reaches its ultimate condition. Therefore, alternative methods are needed to analyze the nominal capacity of concrete-steel deck slab. This study compares three different nominal capacity analysis methods to a laboratory test result. Those methods are ultimate, working stress, and SDI-ANSI (2017). The average error value of those three methods compared to laboratory test results in 35,57%, 9,48%, and -10,31% for ultimate, working stress, SDI-ANSI (2017) consecutively.it can be concluded the working stress method is the most accurate. However, SDI-ANSI (2017) is the conservative one, while the ultimate method is not recommended to analyze the concrete-steel deck slab's nominal capacity.